63 772
Assignments Done
99,3%
Successfully Done
In August 2018

Answer to Question #8069 in Real Analysis for Mike

Question #8069
Show that K(x-a) = O(k-a) [this is the letter O no the number 0] for any K.
Expert's answer
K(x-a) = O(k-a) x->x0 <=> exists C>0 and exists eps>0: |K(x-a)|<|C(x-a)|, xε(x0-eps,x0+eps). So, let's assume C:=K+1 and eps:=1 for any K.

Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be first!

Leave a comment

Ask Your question

Submit
Privacy policy Terms and Conditions